Mapeamento termográfico como instrumento de avaliação da dor neuropática em mãos e pés de pacientes com hanseníase - Tiago, Liliane Marques de Pinho (2021)
Introduction: Leprosy is an infectious disease that mainly affects the skin and peripheral nerves, although curable and of a well-defined cause, is still a public health problem in many countries. It is characterized by chronic evolution, having as etiological agent the Mycobacterium leprae. Leprosy peripheral neuropathy leads to changes in motor, sensory and autonomic neural function, and neuropathic pain (NP) is one of the main complications. The management of NP is challenging and involves clinical criteria and neurological tests. Infrared thermography (IRT) has been shown to be effective in evaluating peripheral autonomic function, detecting changes in the flow of cutaneous microcirculation in painful syndromes. Objective: This study aimed to evaluate the function of fine fibers by mapping the temperature of hands and feet of patients with NP. Material and methods: This transversal study evaluated 29 leprosy patients with neuropathic pain (PWP), 26 patients without pain leprosy (PNP) and 20 healthy individuals as a control group. For quantitative evaluation of temperature, regions of interest were defined, 24 in the hands, 17 in the feet and neural areas of the ulnar, radial, median, tibial and fibular nerves. The research subjects were submitted to cold stress test (CST) and thermal images of hands and feet were captured with FLIR camera® T420 IR, before and after the test. Heart rate and blood pressure were also evaluated before, during and after the test. The instruments used in the evaluation of NP were visual analog pain scaleand simplified neurological evaluation. Electroneuromyography (ENMG) was performed to complement the neurological evaluation. Results: The prevalence of NP in this study was 52.7%. In the PWP group, 93.1% of patients reported moderate to severe chronic pain. The most frequent DN4 items in the PWP group were numbness (86.2%), tingling (86.2%) and electric shocks (82.7%). Type 1 reactional episodes were significant in the PWP group (p=0.02). The control group presented higher pain intensity during CST (p=0.006). In the PWP and PNP groups, 86.3% (46/55) of the patients had a predominance of multiple mononeuropathy in the ENMG, 80% (44/55) presented sensory loss and 69.1% (38/55) had some degree of disability. Before CST, the PWP and PNP groups presented significant temperature asymmetry in almost all points evaluated in the hands, except in two palm points and one dorsal point. And in the feet, they presented significant asymmetry in all points, indicating a greater involvement of the lower limbs (p<0.05). After CST, there was temperature asymmetry during thermal recovery in the neural areas of the median nerves (p = 0.008) in the PWP group and in the neural areas of the ulnar, radial, and median nerves (p <0.05) in the PNP group. Only the PWP group did not present a reduction in mean temperature in the tibial and fibular neural areas after CST. The three study groups showed positive cardiac response during CST. Conclusion: Thermal mapping confirmed the asymmetric pattern of leprosy neuropathy, indicating a change in the function of the autonomic nervous system and showing a useful method in the approach to patient with pain.